THE USE THINK PAIR SHARE TO IMPROVE STUDENTS’ READING COMPREHENSION AT THE NINTH GRADE STUDENTS OF JUNIOR HIGH SCHOOL ERA IBANG MEDAN - Mahdalena, Evi Kristin; Simamora, Rosa Maria; Ginting, Fiber Yun A (Kairos English Language Teaching Journal, 2020)
This research is conducted in order to improve students’ reading comprehension in the easiest way through using think pair share of the ninth grade students of Junior High School Era Ibang Medan, and it also help the English teacher of the ninth grade students of Junior High School Era Ibang Medan to managed activities in classroom.In conducting this research, the researcher used Classroom Action Research (CAR) as the method of research. This research consisted of two cycles and each cycle consisted of four steps, they were planning, action, observation and reflecting. Each cycle was conducted in three meetings, so the researcher conducted this researcher in six meetings for one month and two weeks. The data were in the form of qualitative and quantitative data. The qualitative data was analyze the learning teaching process. The quantitative data was to count the students’ score in pre-test and post-test.The result of this research shows that using think pair share of the ninth grade students of Junior High School Era Ibang Medan could improve their reading skills. The students’ responses showed that they were interested in learning reading through think pair share. Morever, the students’ achievements in pre-test and post-test showed a significant improvement. The students’ average score in pre-test was 53,19%, while in the formative test in cycle I, the students’ average score is 60,03, and in the post-test cycle II, the students’ average score is 76. That means the think pair share can improve the students’ reading skill.